2020
DOI: 10.1111/sode.12497
|View full text |Cite
|
Sign up to set email alerts
|

Group bias in children’s rectification of inequality using resources of different values

Abstract: Previous research has found that children can engage in rectification of pre-existing inequality by allocating more resources to individuals and groups of disadvantaged status, but less research has investigated how children address the inequalities using resources of different values, especially when they are linked to group membership (i.e., in-group or out-group member) in the first-party (Study 1) and third-party contexts (Study 2). To address these issues, children aged 5-6 years How children will react t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…Specifically, children who lost were not willing to sacrifice their own interests and continued to make more equal allocations that were beneficial for themselves, whereas children who won adhered to more merit‐based allocations that were consistent with social norms and satisfied their self‐interest. Combined with the result that equal allocators were more likely to reference self‐interest at a young age and that all of the reversal allocators tended to use self‐interest (except for others ) to explain their allocating behaviours in the lose condition, we speculated that the participants were affected by self‐interest after interpersonal competition (Kanngiesser & Warneken, 2012; Pappert et al., 2017; Shaw et al., 2012), although they could gradually inhibit this tendency during allocation with age (Fehr et al., 2008; Sheskin et al., 2016; Xiao et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, children who lost were not willing to sacrifice their own interests and continued to make more equal allocations that were beneficial for themselves, whereas children who won adhered to more merit‐based allocations that were consistent with social norms and satisfied their self‐interest. Combined with the result that equal allocators were more likely to reference self‐interest at a young age and that all of the reversal allocators tended to use self‐interest (except for others ) to explain their allocating behaviours in the lose condition, we speculated that the participants were affected by self‐interest after interpersonal competition (Kanngiesser & Warneken, 2012; Pappert et al., 2017; Shaw et al., 2012), although they could gradually inhibit this tendency during allocation with age (Fehr et al., 2008; Sheskin et al., 2016; Xiao et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that with age, children can gradually overcome the negative impact of equality and self or group interests when conducting allocations (McAuliffe & Dunham, 2017; Rizzo et al., 2018, 2020; Xiao et al., 2019). One explanation is that with age, there is increasing personal experience with moral norms emphasizing the importance of allocating fairly and towards social norms of the wrongfulness of self‐interest and intergroup discrimination (Elenbaas et al., 2016; Elenbaas & Killen, 2016; Xiao et al., 2021). An alternative explanation is that with increasing group interaction experience, children become more concerned with maintaining and defending their social reputation, especially in the setting of this research, where children had to represent their class to compete and allocate with persons who were in the same grade and same school (Robbins & Rochat, 2011; Yazdi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies have yielded relatively consistent findings in third-party contexts, the question of how children allocate resources to high-versus low-merit collaborators in first-party contexts, where self-interest is affected directly, remains unclear (Rochat et al, 2009;Sheskin et al, 2016;Xiao et al, 2021). Hamann et al (2014) asked pairs of 3.5-year-old children to cooperate to obtain rewards by pulling ropes.…”
Section: Children's Merit-based Resource Allocation In the Collaborat...mentioning
confidence: 99%
“…When specific attributions for resource disparities are not provided, by ages 7–8, children use equity to guide their resource allocation decisions (Rizzo & Killen, 2016; Rutland & Killen, 2017). For example, when children ages 7 and above are presented with an inequality between two groups, they tend to rectify the inequality between the groups and give more to the disadvantaged group (e.g., Elenbaas et al, 2016; Elenbaas & Killen, 2016; Shaw & Olson, 2012; Xiao et al, 2021). However, these patterns of distributive justice can shift when explanations for a disparity are provided; children ages 3–8 are more likely to perpetuate an inequality when the inequality is attributed to an internal, individual cause (i.e., effort) as compared to an external, structural cause (i.e., gender discrimination; Rizzo et al, 2020).…”
mentioning
confidence: 99%